Pre-pregnancy body mass index and glycated-hemoglobin with the risk of metabolic diseases in gestational diabetes: a prospective cohort study - Wang, Xinyue; Zhang, Simin; Yu, Wenlu; Li, Guohua; Li, Jinglin; Ji, Jing; Mi, Yang; Luo, Xiaoqin (Frontiers in Endocrinology, 2023)
Background: Metabolic diseases during pregnancy result in negative consequences for mothers. However how Pre-pregnancy body mass index (BMI) and late-pregnancy glycated-hemoglobin (HbA1c) affect the combined risk of other metabolic diseases in women with GDM is unclear. The study aims to investigate the influence of pre-pregnancy BMI and pregnancy glycemic levels on other gestational metabolic diseases in women with GDM. Methods: Pregnancies with GDM from January 2015 to December 2018 in the Xi'an longitudinal mother-child cohort study (XAMC) were retrospectively enrolled. Those without other metabolic diseases by the time of oral glucose tolerance test (OGTT) detection were finally recruited and divided into four groups by pre-pregnancy BMI (Underweight <18.5kg/m 2; Normal weight 18.5-23.9 kg/m 2; Overweight 24.0-27.9 kg/m 2; Obesity ≥28.0 kg/m 2, respectively) or two groups by HbA1c in late pregnancy (normal HbA1c<5.7%; high HbA1c≥5.7%). Multivariate logistic regression analysis was used to identify risk factors. Interaction between pre-pregnancy BMI (reference group 18.5-23.9 kg/m 2) and HbA1c (reference group<5.7%) was determined using strata-specific analysis. Results: A total of 8928 subjects with GDM were included, 16.2% of which had a composite of metabolic diseases. The pre-pregnancy overweight and obesity, compared with normal BMI, were linked to the elevated risk of the composite of metabolic diseases, particularly pre-eclampsia (both P <0.001) and gestational hypertension (both P<0.001). Meanwhile, patients with high HbA1c had an obvious higher risk of pre-eclampsia (P<0.001) and gestational hypertension (P= 0.005) compared to those with normal HbA1c. In addition, there were significant interactions between pre-pregnancy BMI and HbA1c (P<0.001). The OR of pre-pregnancy BMI≥ 28 kg/m 2 and HbA1c≥5.7% was 4.46 (95% CI: 2.85, 6.99; P＜0.001). The risk of other metabolic diseases, except for preeclampsia (P=0.003), was comparable between the two groups of patients with different HbA1c levels at normal pre-pregnancy BMI group. However, that was remarkably elevated in obese patients (P=0.004), particularly the risk of gestational hypertension (P=0.004). Conclusions: Pre-pregnancy overweight/obesity and late-pregnancy high HbA1c increased the risk of other gestational metabolic diseases of women with GDM. Monitoring and controlling late-pregnancy HbA1c was effective in reducing metabolic diseases, particularly in those who were overweight/obese before conception.